Does team competition increase pro-social lending? Evidence from online microfinance - Roy Chen; Yan Chen; Yang Liu; Qiaozhu Mei (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2014)
We investigate the effects of team competition on pro-social lending activity on Kiva.org, the first microlending website to match lenders with entrepreneurs in developing countries. Using naturally occurring field data, we find that lenders who join teams contribute 1.2 more loans (30-42) per month than those who do not. To further explore factors that differentiate successful teams from dormant ones, we run a large-scale randomized field experiment (n = 22, 233) by posting forum messages. Compared to the control, we find that lenders make significantly more loans when exposed to a goal-setting and coordination message, whereas goal-setting alone significantly increases lending activities of previously inactive teams. Our findings suggest that goal-setting and coordination are effective mechanisms to increase pro-social behavior in teams.
Keywords: C1; C93; D64; H41; 330; social identity; pro-social lending; microfinance; field experiment